Hydroeconomic optimization for canal-well conjunctive irrigation and drainage management in an arid region with salinization - Cao, Zhaodan; Zhu, Tingju; Li, Baofu; Yan, Yuhan; Luo, Yuanyuan; Chen, Yanfeng; Pan, Tao (Frontiers in Sustainable Food Systems, 2025)
Formulating sustainable canal-well conjunctive irrigation and drainage strategies remains a critical challenge for arid irrigated agriculture confronting with water scarcity and salinization, primarily due to the multifaceted impacts of such strategies on water-land allocation, water-salt dynamics, agricultural profitability and food security. This study developed an integrated hydroeconomic optimization framework for canal-well conjunctive irrigation and drainage management by integrating agro-hydrological processes (inter-annual root-zone/groundwater water-salt dynamics, salinity-stressed crop yield assessment, canal-well conjunctive irrigation module) into an economic optimization framework. Positive Mathematical Programming (PMP) was employed to calibrate the hydroeconomic framework to base-year observations, enabling it to capture farmers’ adaptive decisions under policy interventions. The framework was run continuously over a 15-year horizon under strategies defined by groundwater drainage capacity (α) and surface-to-groundwater irrigation area ratio (SGIAR) in the Hetao Irrigation District (HID). We assessed the impacts of these strategies on optimal cropping pattern and water allocation decisions, and the consequent feedback effects of these decisions on water-salt dynamics, agricultural profitability, and food security. Results show reducing SGIAR by 70% expands grain areas, enhances food security, reduces root-zone/groundwater salinity by 9.2%/8.0%, and saves 9.7% total conjunctive water consumption. In contrast, increasing SGIAR undermines food security. Enhancing α to 0.21 annually mitigates salinization and boosts productivity and benefits. Notably, the “10% SGIAR reduction and α = 0.21” scenario emerges as a sustainable strategy which annually increases net benefits, alleviates salinization, conserves water, sustains food security, and ensures groundwater sustainability. This study offers a hydroeconomic framework and policy insights for advancing sustainable irrigated agriculture in the HID and analogous arid irrigated systems worldwide.